2020
DOI: 10.3390/biom10020338
|View full text |Cite
|
Sign up to set email alerts
|

Acorus gramineusand and Euodia ruticarpa Steam Distilled Essential Oils Exert Anti-Inflammatory Effects Through Decreasing Th1/Th2 and Pro-/Anti-Inflammatory Cytokine Secretion Ratios In Vitro

Abstract: To clarify the effects of steam distilled essential oils (SDEO) from herbs used in traditional Chinese medicine on immune functions, two potential herbs, Acorus gramineusand (AG) and Euodia ruticarpa (ER) cultivated in Taiwan, were selected to assess their immunomodulatory effects using mouse primary splenocytes and peritoneal macrophages. T helper type 1 lymphocytes (Th1) (IL-2), Th2 (IL-5), pro-inflammatory (TNF-α) and anti-inflammatory (IL-10) cytokines secreted by correspondent immune cells treated with SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Additionally, it was confirmed that IgA and IgG are produced in higher quantities by the peripheral blood mononuclear cells of healthy people who consume wine polyphenols [ 18 ]. Polyphenols generally improve the Th1/Th2 cytokine balance, leading to cellular immunity dominating over humoral immunity and the subsequent inflammatory response that causes inflammation [ 19 , 20 ]. They also play a role in the release of cytokines required for cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was confirmed that IgA and IgG are produced in higher quantities by the peripheral blood mononuclear cells of healthy people who consume wine polyphenols [ 18 ]. Polyphenols generally improve the Th1/Th2 cytokine balance, leading to cellular immunity dominating over humoral immunity and the subsequent inflammatory response that causes inflammation [ 19 , 20 ]. They also play a role in the release of cytokines required for cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Splenocytes and peritoneal macrophages were isolated from female BALB/c mice and respectively adjusted to 1 × 10 7 cells/mL and 2 × 10 6 cells/mL in tissue culture medium (TCM medium) [ 2 , 29 ]. Conditioned media using primary immune cells including splenocytes and macrophages in the absence or presence of GSPS, GSF1, GSF2, and GSF3 at the indicated final optimal concentrations of 0, 8, 40, and 200 μg/mL were prepared and performed as described previously [ 2 , 5 , 18 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Th2 cells secrete IL-13, IL-4, IL-5, IL-10, and TGF-β to maintain immunological tolerance. A balance between Th1 and Th2 cells is important for human health ( Yeh and Lin, 2020 ). The imbalance between Th1 cell- and Th2 cell-secreted cytokines is a key driver in the pathogenesis of MS ( Sospedra and Martin, 2005 ; Hirahara and Nakayama, 2016 ).…”
Section: Regulation Of T Cell Differentiationmentioning
confidence: 99%